7 Collaboration between palliative and critical care: a review of end of life care for patients with COVID-19 on the critical care unit. Issue Volume 11: Issue (2021)Supplement 1 (16th March 2021) - Fleming, Elizabeth; Dykes, George; Frew, Katie; Snell, David
Abstract : Introduction: Providing end of life care for patients with COVID-19 on the Critical Care Unit (CCU) is complex. The novelty of disease symptomology and the impact of visiting restrictions pose significant new challenges for Palliative and Critical Care services. This review analyses end of life care for people with COVID-19 on the CCU during the first wave of the pandemic. Methods: All patients in a regional hospital who received continuous positive airway pressure (CPAP) or invasive ventilation (IV) and subsequently died on the CCU were included (n=23). Data were collected through retrospective review of clinical notes. Results: 15 patients received IV. Eight received CPAP only. Two were subsequently stepped down to high flow nasal cannula (HFNC). All patients died within 24 hours of withdrawal of respiratory support. Nine people who received IV died within one hour of treatment withdrawal. Patients who required CPAP had a high burden of symptoms including breathlessness (n=8), delirium/agitation (n=5) and anxiety/fear (n=4). Five patients requested removal of CPAP. In the last 24 hours of life all eight patients on CPAP/HFNC required an opioid. Six also required midazolam. Only two patients had syringe drivers prescribed. All patients who were recognised as being in the last days of life had discussions documented between healthcare professionals and their relatives (n=20). Conclusions: Patients treated on the CCU for COVID-19 demonstrated a high symptom burden. Time from withdrawal of ventilation to death was short. Medications required varied and the use of syringe drivers was low. This may indicate a need for earlier collaboration between Critical Care and Palliative Care teams. Despite complexities surrounding care provision in this setting there was a high standard of documented discussions with patients and families. This review highlights the need for early recognition of people being â€œsick enough to dieâ€ to ensure good quality, individualised end of life care.